The Improvement of Learning Outcomes on Bump Pass of Volleyball (The Application of Difficulty Level Approach on Students of Sport Coaching Education Department in FIK UNIMA) - Christianti Anggraini Motto; Nolfie Piri; Fredrik Alfrets Makadada (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study aims to find out the improvement of learning outcomes on bump pass of volleyball. The research subjects in this study were 30 students of grade A Semester IV, Department of Sports Training Education at Universitas Negeri Manado. This study shows that that there is an improvement in bump pass learning outcomes through lectures with a level of difficulty in students of Sport Education Department at FIK UNIMA. In the first cycle students were quite enthusiastic in attending the bump pass lectures. In accordance with the reflection, the average of bump pass volleyball class is 72 with the percentage of completeness 66.7% of students completed and student learning outcomes in the second cycle is 78 with a percentage of completeness of 86.7% it can be concluded that there is a significant improvement in learning outcomes in cycle II.